2001
DOI: 10.1023/a:1012506426440
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of intravenous pamidronate and oral clodronate on symptoms and bone resorption in patients with metastatic bone disease

Abstract: Intravenous pamidronate appears to be more effective than oral clodronate in both controlling symptoms and suppressing bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 26 publications
0
65
0
3
Order By: Relevance
“…This may also explain the pain control obtained in a randomised controlled trial that favoured intravenous pamidronate over oral clodronato. 20 The severity of the disease may be an important issue for debate when 21 who failed to show improvement in pain control after adjuvant clodronate vs mitoxantrone. He had an analgesic response (450% decrease in analgesic intake from baseline) in 33% out of 104 cases using clodronate and 30% in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…This may also explain the pain control obtained in a randomised controlled trial that favoured intravenous pamidronate over oral clodronato. 20 The severity of the disease may be an important issue for debate when 21 who failed to show improvement in pain control after adjuvant clodronate vs mitoxantrone. He had an analgesic response (450% decrease in analgesic intake from baseline) in 33% out of 104 cases using clodronate and 30% in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients on the study received oral clodronate and this response rate is consistent with previous data with this drug. Higher biochemical response rates would be expected with more potent IV bisphosphonates (Vinholes et al, 1997;Jagdev et al, 2001). A proportion of the patients (approximately 21%) had already been on bisphosphonates prior to study entry and may have already achieved a biochemical response.…”
Section: Biochemical Response and Follow-up For Longer Than 6 Monthsmentioning
confidence: 99%
“…A study by Vinholes et al (1996) showed a significant correlation between metastatic bone pain and bone resorption. Several subsequent studies in both breast and prostate cancer patients have confirmed this initial finding (Jagdev et al, 2001). Both oral and intravenous bisphosphonate therapy have been shown to reduce Ntx levels and, importantly, only those patients who showed normalisation of bone resorption following bisphosphonate treatment experienced clinical benefit in terms of an improvement in pain, analgesic use and morbidity (Vinholes et al, 1997).…”
mentioning
confidence: 91%
“…In addition, the inhibitory activity of bisphosphonates on bone resorption may be indirectly mediated by other cells such as cells of the osteoblastic lineage or the macrophage family (Sahni et al, 1993;Nishikawa et al, 1996;Vitte et al, 1996;Siwek et al, 1997;Fromigue and Body, 2002). On the other hand, we and others (Fromigue et al, 2000;Senaratne et al, 2000;Jagdev et al, 2001b) previously showed that bisphosphonates can induce human breast cancer cell death in vitro (apoptosis and/or necrosis), which could contribute to their beneficial clinical effects. Thus, bisphosphonates exhibit beneficial effects on bone integrity by reducing bone resorption induced by osteoclasts and maybe also by direct 'antitumoral' effects.…”
mentioning
confidence: 92%